Analisis Kebijakan Sistem Rekapitulasi pada Pemilihan Kepala Daerah dan Wakil Kepala Daerah Serentak Tahun 2020 di Indonesia - Al Alamudi, Arifin; Situmorang, Tonny P.; Fauzan, Indra (PERSPEKTIF, 2024)
The 2020 Simultaneous Regional Head Election (Pilkada Serentak) in Indonesia was a landmark moment with the introduction of the Recapitulation Information System (Sirekap) by the General Election Commission (KPU). Despite facing challenges such as complicated installation and activation, network constraints, and lack of user understanding, this study examines how the KPU implemented Sirekap. Using qualitative methods, data were collected through interviews, observations, documentation, and literature review. The results show that KPU conducted a comprehensive policy analysis in using Sirekap. First, the problem is defined by emphasizing the importance of information technology to increase public trust and speed up recapitulation. KPU conducted academic studies and collaboration with universities. Second, future forecasting shows Sirekap as a trial for the 2024 elections with a series of simulations to convince the legislature. Third, the House of Representatives approved the use of Sirekap as a trial in the 2020 Regional Elections. Fourth, policy monitoring is carried out through the issuance and refinement of operational and technical guidelines up to two days before the election. Finally, policy evaluation resulted in the book “Sirekap Road Map 2024” in 2021 as a guide for organizing the 2024 elections. This research concludes that the KPU has taken detailed and organized steps in the implementation of Sirekap in the 2020 Simultaneous Regional Elections, in order to increase effectiveness, efficiency, and transparency in elections in Indonesia.